Patient's Adherence and Compliance and Quality of Life During/After VIT - Incorvaia, Cristoforo; Heffler, Enrico; Peveri, Silvia; Pucciarini, Francesco; Canonica, Giorgio Walter; Ridolo, Erminia (Frontiers in Allergy, 2022)
Adherence and compliance, respectively considered as a more positive, proactive behavior, resulting in a patient's lifestyle change to follow a daily regimen, and, as a more enforced response to an external command, are a critical aspect of any medical therapy, since it is estimated that less than half of the patients who are prescribed a therapy perform it, respecting the doses and duration. As far as aeroallergen immunotherapy is concerned, current data show that adherence is respected in about 50% of subcutaneous immunotherapy and in percentages even lower than 20% in sublingual immunotherapy treatments. This review analyzes the adherence to venom immunotherapy (VIT), in which, given its purpose of preventing potentially fatal anaphylactic reactions to insect stings, this aspect plays a critical role. In fact, protection from stings already takes place when the maintenance dose is reached, but VIT interruption before the recommended duration of 5 years exposes patients to new sting reactions. The data on adherence to VIT are far less abundant than that for aeroallergen immunotherapy. One of the first studies reported poor adherence in Austria, but the model used, consisting in the estimate of the percentage of patients with systemic reactions who accepted or rejected VIT, does not meet the criteria that define adherence to treatment. As for appropriate adherence studies, rates higher than 70% were reported in the United States and European countries. Studies from Italy found that good adherence were observed also in patients receiving, after 4 years of VIT, 3 months extended maintenance dose, as well as in patients treated during the COVID-19 pandemic, <10% of whom stopped VIT. Instead, only 35% of the patients treated for allergy to imported fire ant remained adherent after 1 year of treatment. However, also concerning honeybees and vespids, although adherence is satisfactory, it is possible to further improve it by increasing information and support for patients. Health-related quality of life (HRQL) is an efficient measure to estimate the effectiveness and safety of medical treatment. Tools designed to make patients aware of its improvement through VIT and, in particular, of the complete prevention of the risk of fatal reactions have an important role in reinforcing adherence. However, aspects not yet evaluated, such as the possible relationship between the efficacy of VIT and HRQL or its particular features in patients with mastocytosis, deserve specific studies.